Behavioral and Technological Determinants of Cash Waqf ‎Intention on Crowdfunding Platforms - Hakiem, Hilman; Sumarwan , Ujang; Tanjung , Hendri; Saptono‎, Imam Teguh (International Journal of Accounting and Economics Studies, 2025)
This study examines the determinants of Muslims’ intention to contribute to cash waqf through crowdfunding platforms by integrating behavioral, spiritual, and technological perspectives. Using the Theory of Planned Behavior (TPB) and the Unified Theory of Acceptance and ‎Use of Technology 2 (UTAUT2), it proposes and empirically tests an integrated structural model. Data were collected in 2025 from 274 ‎Indonesian respondents via purposive and snowball sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS ‎SEM). The results reveal that religiosity, awareness, and behavioral beliefs strongly influence donors’ attitudes, while control beliefs and ‎habit significantly predict intention. Promotion and socialization enhance knowledge and awareness, which in turn mediate positive behavioral outcomes. Conversely, performance expectancy, effort expectancy, and price value show weaker direct effects, highlighting that trust, ‎familiarity, and moral conviction outweigh utilitarian motivations. Respondents demonstrate high religiosity and positive perceptions of ‎digital waqf mechanisms, indicating readiness for fintech-based philanthropy. Strategic recommendations include enhancing transparency, ‎strengthening religious and financial literacy, and fostering habitual digital engagement. Overall, the findings contribute to Islamic social ‎finance by offering a holistic model explaining how psychological motivations and technological acceptance jointly shape participation in ‎digital cash waqf ecosystems‎.
Keywords: Behavioral Intention; Cash Waqf; Crowdfunding; Fintech Adoption; Religiosity